Manajemen Jadwal Proyek dan Karyawan Berbasis Web Pada PT. Bee Solution Partners - Destyan Shorea Permatasari; Daniel Jahja Surjawan (Maranatha University Press, 2017)
PT. Bee Solution Partners is one of the IT solution company in Bandung. At present, PT. BSP does not have any system to display employee profile, and does not have any system to help project manager maintaining projects either. Project Management Information System is built for helping Human Resource Department (HRD) Staff in employee data management which can be improved as employee profile, and also helping project manager in project management. There are some features provided in Web Based Project Management Information System at PT. BSP such as CSV file upload, profile management, and generate project schedule